Testing the relation between dispositional optimism and conditioned pain modulation: Does ethnicity matter? - Goodin, Burel R. (2012)
Greater dispositional optimism has been related to less severe pain; however, whether optimism is associated with endogenous pain modulation has not yet been examined. The beneficial effects of dispositional optimism often vary according to cultural dynamics. Thus, assessing optimism-pain relationships across different ethnic groups is warranted. This study sought to examine the association between optimism and conditioned pain modulation (CPM), and test whether this association differs according to ethnicity. Optimism and CPM were assessed in a sample of healthy, ethnically diverse young adults. CPM was determined by comparing pressure pain thresholds obtained before and during exposure to a cold pressor task. All participants completed a validated measure of dispositional optimism. Greater reported optimism was significantly associated with enhanced CPM, and the strength of this association did not vary according to individuals’ ethnic background. These findings suggest that an optimistic disposition may potentiate endogenous pain inhibition.